2019
DOI: 10.1080/03007995.2019.1628562
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact and chronic obstructive pulmonary disease outcomes of a comprehensive inhaler to nebulization therapy protocol implementation in a large multi-state healthcare system

Abstract: Objective: There are currently 39 FDA-approved metered-dose (MDI) or dry-powder inhalers (DPI) on the US market. Most are high cost with significantly more drug in the device than needed for a typical average length of stay in acute care hospitals, which leads to significant waste. The objective was to assess the financial impact and chronic obstructive pulmonary disease (COPD) outcomes of a comprehensive inhaler to nebulization protocol implemented in a large multi-state US health system. Methods: The retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The significant reduction in respiratory drug costs have previously been reported secondary to the implementation of our inhaler to nebulization protocol as well as the high percentage of overall nebulized budesonide costs throughout the health system. 7 Our institution also observed annual nebulized budesonide expenditures of $175 924, accounting for 52% of our overall inhaler and nebulized medication drug costs of $338 532 in 2018. The significant occurrence of duplicative therapy of ICS and systemic corticosteroids in our respiratory patients ultimately led to the development, approval, and implementation of the automatic budesonide discontinuation protocol, as stated.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The significant reduction in respiratory drug costs have previously been reported secondary to the implementation of our inhaler to nebulization protocol as well as the high percentage of overall nebulized budesonide costs throughout the health system. 7 Our institution also observed annual nebulized budesonide expenditures of $175 924, accounting for 52% of our overall inhaler and nebulized medication drug costs of $338 532 in 2018. The significant occurrence of duplicative therapy of ICS and systemic corticosteroids in our respiratory patients ultimately led to the development, approval, and implementation of the automatic budesonide discontinuation protocol, as stated.…”
Section: Discussionmentioning
confidence: 71%
“…5,6 Another study has illustrated significant hospitalized ICS medication costs in COPD treatment. 7 If ICS medications can be discontinued without incurring negative effects to the patient and LOS while patient’s are on systemic steroids, a closer look into combined use of systemic and inhaled corticosteroids is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…It is plausible that additional resources, specifically respiratory therapists, may be required to administer and supervise the increase in nebulized medication orders described in this study; however, previous studies describing similar expansions of medication formularies and nebulizer protocols did not identify a need to hire more staff based on their findings. 10,23 Nonetheless, the direct cost savings attributable to revefenacin must be carefully weighed against indirect caregiving costs attributable to and direct wages incurred by its caregiving burden on respiratory therapists.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with preimplementation, system-wide drug expenditures declined by approximately 40% in post-implementation years 1 and 2. 35 On the other hand, a cohort study at a single US hospital showed that reducing nebulizer use, and implementing MDIs in the hospital resulted in significant savings annually. However, some limitations of this study included a lack of control group and possible overestimation of cost-savings since some of the costs were semifixed.…”
Section: Nebulized Drug Therapymentioning
confidence: 99%